Relationship between Service Quality and Behavioral Intentions: The Mediating Effect of Customer Satisfaction - Azman Ismail; Ilyani Ranian Rose; Rabaah Tudin; Norazryana Mat Dawi (ETIKONOMI, 2017)
This study was undertaken to measure the relationship between service quality, customer satisfaction and behavioral intentions. A survey method was employed to collect data from customers who received treatments at army medical organizations in Malaysia. The outcomes of Smart-PLS path model analysis confirmed that relationship between service qualities features (tangible, reliability, responsiveness, assurance and empathy) with customer satisfaction were positively and significantly correlated with behavioral intentions. This result demonstrates that effect of tangible, reliability, responsiveness, assurance and empathy on behavioral intentions was mediated by customer satisfaction.DOI: 10.15408/etk.v16i2.5537